The EUROLIGHT cluster headache project: Description of methods and the study population - An Internet-based cross-sectional study of people with cluster headache - Colette Andrée; Andreas R Gantenbein; Peter S Sandor; Jean Schoenen; Heiko Pohl (SAGE Publishing, 2019)
Objective: To present the methodology and to describe the sample of a large, Internet-based survey on the burden of cluster headache (CH). Methods: Participants filled out a questionnaire online. Inclusion criteria were a reported diagnosis of CH and a residency in a European country; exclusion criteria were refusal to give informed consent and to complete the questionnaire. Results: A total of 1514 participants completed the questionnaire. Of these, 66.2% were male and 31.2% reported suffering from chronic CH. The diagnosis was validated based upon the responses in 92.9% of the participants. Other diagnoses seemed more likely in 0.8%. Among the participants with self-reported chronic CH, the International Classification of Headache Disorders-3 beta criteria for chronicity were fulfilled by 90.8%. Conclusions: In this article, we discuss the applied methodology as well as the properties of the sample. The overall accuracy of the self-reported diagnoses was very good as judged by our questionnaire; women and chronic CH were slightly over-represented. We will present the results of more thorough analyses in future articles and believe that these data will provide deeper insights into the burden of CH and will help to give a voice to those who endure this painful disease.